2021
DOI: 10.3390/jcm10245895
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Faceted Evaluation of Impulsivity Traits and Early Maladaptive Schemas in Patients with Anorexia Nervosa

Abstract: (1) Background: patients with Anorexia Nervosa (AN) are classified either as restrictive (ANr) or binge/purge (ANbp) according to the absence or presence of impulsive eating and compensatory behaviors. The aim of the present study was to assess the levels of impulsivity in both AN subtypes and to explore whether individual differences in impulsivity may be explained by differences in the presence of early maladaptive schemas. (2) Methods: the sample group included 122 patients with ANr, 112 patients with ANbp,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…CRT was also found to be a useful supplement to as usual care (Leppanen et al, 2018) and seems especially beneficial for patients with poor baseline cognitive abilities (Dingemans et al, 2014;Tchanturia et al, 2014). Moreover, rolling group CRT in 31 mostly young adults (mean age: 20.5 � 4.5 years, range: 15-30 years) supported the value of CRT in a quasiexperimental design against historical controls (n = 28), reporting significantly greater improvements of the CRT group in clinical symptomatology, flexibility, selfconfidence about the ability to change, and less shortterm focus, without differences between restrictive and binge-purging AN subgroups (Meneguzzo et al, 2021).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…CRT was also found to be a useful supplement to as usual care (Leppanen et al, 2018) and seems especially beneficial for patients with poor baseline cognitive abilities (Dingemans et al, 2014;Tchanturia et al, 2014). Moreover, rolling group CRT in 31 mostly young adults (mean age: 20.5 � 4.5 years, range: 15-30 years) supported the value of CRT in a quasiexperimental design against historical controls (n = 28), reporting significantly greater improvements of the CRT group in clinical symptomatology, flexibility, selfconfidence about the ability to change, and less shortterm focus, without differences between restrictive and binge-purging AN subgroups (Meneguzzo et al, 2021).…”
Section: Introductionmentioning
confidence: 60%
“…In summary, the present study revealed no superiority of CRT over NSCT with regard to cognitive flexibility, central coherence and self-reported everyday-life functions in female adolescents with AN. In light of these findings, and despite some recent negative evidence for CRT in adults, it appears that comparable studies in older AN patients with a longer duration of illness cannot be directly applied to adolescent populations with AN, underscoring the need of future research to identify the core purpose and expected outcomes of CRT in this specific younger age group (Giombini et al, 2018;Giombini, Nesbitt, Kusosa, Fabian, et al, 2022;Giombini, Nesbitt, Kusosa, Hinallas, et al, 2022;Lindvall Dahlgren & Stedal, 2017;Meneguzzo et al, 2021;Tchanturia et al, 2017). According to our findings, it appears especially valuable to further investigate the potency of CRT with regard to clinical measurements aside from neuropsychological test performance Tchanturia et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…From the findings presented in this study, we consider that there were also limitations such as: the clarity of the participants' diagnosis, as well as the subtype of psychopathology presented in each of the disorders evaluated and the evaluation of pathognomonic variables of ED ( 158 ) and OCD within the structural model. These limitations could be assessed in future research to make the results more consistent, even with longitudinal designs.…”
Section: Discussionmentioning
confidence: 96%
“…An indirect explanation could be that some patients did not answer because they preferred not to disclose personal information to physicians or their parents. As a recent study on impulsivity traits and early maladaptive schemas in individuals with Anorexia Nervosa (AN) document, restraint may represent a distinguishing feature in AN patients [ 45 ]. People with AN, and with ED in general, may be exposed to stigmatizing attitudes and beliefs, as reported in the context of communities of undergraduate students [ 46 ] and healthcare students [ 47 ].…”
Section: Discussionmentioning
confidence: 99%